A identidade do velho no mundo contemporâneo - Campedelli, Mônica Anechini (2009)
This thesis tried to understand the identity of the oldman in the contemporary world. It is known that the old people, in our country, still do part of social minorities, but in the last decades, they are getting great attention in the researches and in the news of media and open up our eyes for the continuity of this process. And that specifically happens in reason of fights for the statement and recognition of their identities, as well the attempt of getting over their problems, and their miserable life condition. Therefore, we intended to obtain subsidies that allow to describe the problems of the understanding of the psyco socials processes that involves the subject of the identity of the oldman in the contemporary world as well as the possible sense of a emancipating metamorphosis, that would happen (or not) in the understanding of their identities. The old ones use the past to update their present. From their historical-social path originates their own identity, constituted by the representation of social papers, papers that will model that identity under the effects of their memory. At the same time the narrative provokes changes in the way as the people understand themselves and the other ones. When producing the narratives it is possible to the oldman "to hear" himself and to speculate about his own experience. This can be a deeply emancipating process contained in the idea of identity as metamorphosis, that the person learns how to build your own history, your life project, creating your own path